Tantangan dan peluang implementasi pendidikan karakter di SMA keagamaan - Suyuti, Suyuti; Yustitia, Prima (Ta’dibuna: Jurnal Pendidikan Islam, 2021)
Character education discourse in Indonesia is still an important study that needs to develop along with the emergence of increasingly complex and complicated social problems. This study aims to explain the implementation of character education during the COVID-19 pandemic, in particular about the opportunities and challenges of implementing character education in three religious-based high schools in East Jakarta. This study uses a descriptive qualitative approach with a case study method. The results of this study indicate that the implementation of character education in the three high schools that became the locus of this research has in common the dominant challenges that emerged during the covid 19 pandemic, namely order and student discipline in online learning that have not been optimal. Although there are similarities in challenges, each of these schools has differences, especially in terms of efforts to develop character education in each school itself. The difference in efforts to develop character education based on the existence of educational institution resources such as teacher human resources, school finance, technological infrastructure, student readiness and the existence of parental support in each school. ABSTRAK Diskursus pendidikan karakter di Indonesia masih menjadi kajian penting yang perlu dikembangkan bersamaan dengan munculnya masalah sosial yang kian kompleks dan rumit. Penelitian ini bertujuan untuk menjelaskan implementasi pendidikan karakter dimasa pademi covid 19, khususnya tentang peluang dan tantangan implementasi pendidikan karakter di tiga SMA berbasis keagamaan di Jakarta Timur. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode studi kasus. Hasil penelitian ini menunjukkan pelaksanaan pendidikan karakter di tiga SMA yang menjadi locus riset ini memiliki tantangan yang dominan muncul dimasa pandemi covid 19 yaitu ketertiban dan kedisiplinan siswa dalam pembelajaran daring yang belum optimal. Kemudian dalam hal upaya mengembangkan pendidikan karakter di masing-masing sekolah dilatari oleh keberadan sumber daya lembaga pendidikan seperti SDM guru, finansial sekolah, sara-prasarana teknologi, kesiapan siswa dan keberadaan dukungan orang tua siswa di masing-masing sekolah.